Philosophical Analysis of Reason in al-Maturidi - Kahveci, Niyazi (KARABUK UNIV, 2020)
Maturidi is a medieval, non-Arab, a Turkish-Islamic theologian, and founder of Maturidiyya creedal sect. The Reason ('aql) of al-Maturidi has currently been so debatable among Turkish theologians to solve modern Islamic problems among Muslims. The theology of al-Maturidi founded a strong stability between the reason and the revelation. Furthermore, he is accepted as a rationalist theologian. In fact, for him, reason is a subordinate to comprehend the revelation. In this article, it is aimed to discover the typology of his Reason, whether it is sufficient to cope with modern religious progress and problems. We utilized the perspectives of disciplines of philosophy of information and phenomenology. The type of Reason Maturidi has utilized is not a philosophical or logical, that is a systematic one, but it is a middle age bon sense, an ordinary common unsystematic and unmethodical public-practical religious reason; that is everyday life thinking. This reason type has been obsolete in the conception areas, by the modern critical systematic philosophical reason. Thereof Maturidi's reason has no enough scope to formulate modern religious paradigms.
Keywords: Islamic Theology; Phenomenology; Kalam; al-Maturidi; Reason; Unsystematic thinking; Arts & Humanities - Other Topics